Edukasi Hipertensi untuk Meningkatkan Kesadaran Pengendalian Tekanan Darah di Posbindu Pos 2 Melati Desa Borongan, Polanharjo, Klaten - Avanilla Fany Septyasari; Devina Dewi (Universitas Muhammadiyah Klaten, 2026)
Hypertension is a major non-communicable disease often referred to as a silent killer because it may occur without noticeable symptoms until complications develop. This community service activity aimed to improve public knowledge and awareness regarding blood pressure control among participants of Posbindu Pos 2 Melati, Borongan Village, Polanharjo District, Klaten Regency. The activity included blood pressure screening, pre-test, hypertension education using PowerPoint presentations and educational hand fans, interactive discussions, post-test, and distribution of educational media. A total of 24 participants attended the activity, while 18 participants completed the pre-test and post-test evaluation. The average knowledge score increased from 81.1 before the education session to 93.3 after the intervention, indicating an average improvement of 12.2 points. These findings indicate that hypertension education can improve participants’ understanding of hypertension prevention, healthy lifestyles, medication adherence, and routine blood pressure monitoring.